A STUDY ON SERVICE QUALITY PERCEPTION OF POLICYHOLDERS ABOUT PRIVATE LIFE INSURANCE COMPANIES IN TIRUNELVELI DISTRICT - Franco, C.Eugine; Meenakshi, I (International Journal of Research -GRANTHAALAYAH, 2017)
Insurance sector plays a very important role in the development of any economy also, as it provides long term funds for infrastructure development and at the same time strengthens the risk taking ability. The current scenario in the insurance industry is a complex and competitive environment tinged with little stability. With the liberalization and globlisation in insurance, service quality has become an important means of differentiation and path to achieve business success. Such differentiation based on service quality can be a key source of competitiveness for insurance companies and hence have implication for leadership in such organizations. With the increasing demands of customer, insurance sector has become competitive. The purpose of the present study is to measure the service quality perception of customers about Private Life Insurance Companies.